PENGARUH LEVERAGE, PERTUMBUHAN PENJUALAN, PROFITABILITAS, DAN UKURAN PERUSAHAAN PADA NILAI PERUSAHAAN MANUFAKTUR PERIODE 2018-2020 - Wibowo, William; Ardiansyah, Ardiansyah (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
This research aims to determine whether there is an effect of leverage, sales growth, profitability and firm size on the value of manufacturing companies listed on the Indonesia Stock Exchange during 2018-2020. The sample was selected using purposive sampling method and the valid data was 36 companies. The data processing technique using panel data regression analysis assisted by the Eviews 12 program. The results of this study indicate that leverage has a significant and positive effect, sales growth has no effect on firm value, profitability and firm size have a significant and negative effect on firm value. The implication of this research is the need for attention to leverage, profitability, and company size in order to increase firm value.